Gambling Attitudes and Financial Misreporting - Christensen, Dane M.; Jones, Keith L.; Kenchington, David G. (Contemporary Accounting Research, 2018)
Abstract We investigate whether attitudes toward gambling help explain the occurrence of intentional misreporting. Similar to gambling, some financial reporting choices involve taking deliberate, speculative risks. We predict that in places where gambling is more socially acceptable, managers will be more likely to take financial reporting risks that increase the likelihood the financial statements will need to be restated. To test this prediction, we exploit geographic variation in local gambling attitudes and find that restatements due to intentional misreporting are more common in areas where gambling is more socially acceptable. This association is even stronger in situations where management is under greater pressure to misreport, including when the firm is close to meeting a performance benchmark, experiencing poor financial performance, or under investment‐related pressure. Furthermore, these results are robust to numerous tests to address omitted variables and endogeneity. Collectively, these findings suggest gambling attitudes help explain the incidence of intentional misreporting.